Patient satisfaction versus retention of implant overdentures with two attachment systems: A randomized trial. (29th October 2018) - de Albuquerque, Rubens Ferreira; Fromentin, Olivier; Lassauzay, Claire; Conceição Pereira Saraiva, Maria da
Abstract: Background: Clinical success with mandibular implant overdentures is highly dependent on a reliable attachment system connecting prosthesis and implants. Purpose: To compare the levels of retention and patient‐based outcomes on implant overdentures retained/supported by cylindrical (LA) and ball (RA) attachment systems overtime and investigate their relationship. Materials and Methods: Attachment retention (Newtons), and patient satisfaction with the treatment, prosthesis stability, and ability to chew (VAS, 100 mm) were assessed in a crossover trial for both attachment systems at baseline, 1 week, 3, 6, and 12 months and compared to preintervention values. Patients' preference was also recorded. Results: Mean retention of worn attachments and patient satisfaction with denture retention assessed in the preintervention phase were 3.2 N (SD 4.9) and 23.5 mm (IQR 6.5‐65.5), respectively. Overall mean retention along the study was higher for RA than LA (difference of 5.0 N, 95%CI: 2.5‐7.6; P = 0.0005), declining significantly overtime ( P < 0.0001), more steeply for the cylindrical attachment. Differences in VAS ratings between attachments were nonsignificant in the crossover phase ( P > 0.05), but general satisfaction, satisfaction with retention, and comfort were significantly higher when compared with preintervention scores ( P < 0.05). Ratings of retention decreased significantly overtime for both systems and earlier for LA than RA. Satisfaction was lower when retention was either too low or too high, although there was large variation in this association. At the end of the study, all participants chose to remain with the attachment system that they had received last. Conclusions: Attachment selection should be based on patients' individual characteristics and expectations as satisfaction with the attachment retention and denture stability vary largely among patients.